Materials, Methods, and Equipment used by General Dentists of Southeastern Iran for Endodontic Treat-ment - M Rafiei; E Moradi Askari; M Sadeghi; M Mollahasani kahdouyi; N Zeini (Islamic Azad University, 2022)
Background and Aim: The present study aimed to evaluate the materials, methods, and equipment used by general dentists in southeastern Iran for endodontic treatments in 2021.   Materials and Methods: In this cross-sectional study, 121 standard questionnaires were distributed among general dentists in Rafsanjan city, Iran. The questionnaire included demographics and questions regarding the type of materials, methods, and equipment selected by general dentists. The collected data were analyzed by SPSS version 22 using the Chi-square test and ANOVA. Results: The response rate of the participants was 83%(n=100); of which, 55% were females and 45% were males. Only 28% of dentists performed pulp vitality tests, and 46% performed sinus tract tracing in case of infection. Cotton rolls were used by 71% for further isolation, apex locator and radiography were used concurrently to determine the working length by 62%, and canal preparation was done by rotary and manual files by 48%. Rotary M3 and ProTaper files were more commonly used by dentists. Electric rotary handpieces were used for canal instrumentation by 64%, and rotary orifice shapers were more commonly used for canal flaring (61%). The most commonly used obturation method was lateral compaction. Most general dentists used formocresol-impregnated cotton pellets for pulpotomy (43%). Half of the dentists used saline for canal irrigation. Calcium hydroxide was the most commonly used intracanal medicament (87%), and 53% used polymerized sealers. Conclusion: General dentists evaluated in this study violated some of the standards and need to take more training courses.